Homework Help

Compositon xoy=(x-6)(y-6)+6 Calculate 1o2o3o----o2013

user profile pic

ruals | Salutatorian

Posted July 3, 2013 at 4:23 PM via web

dislike 1 like

Compositon xoy=(x-6)(y-6)+6

Calculate 1o2o3o----o2013

1 Answer | Add Yours

user profile pic

justaguide | College Teacher | (Level 1) Adjunct Educator

Posted July 3, 2013 at 4:44 PM (Answer #1)

dislike 1 like

The functions x and y are defined such that xoy = (x - 6)(y - 6) + 6

Consider the value of 6oy, 6oy = (6 - 6)(y - 6) + 6 = 6

Similarly xo6 = (x - 6)(6 - 6) + 6 = 6

If 1o2o3o4o5 = x and 7o8o9o...2013 = y

1o2o3o...o2013

= xo6oy

as xo6 = 6

= 6oy

as 6oy = 6

= 6

The value of 1o2o3o...o2013 = 6

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes